Study of total duration of distal compound muscle action potential in demyelinating and axonal Guillain-Barre' syndrome. (3rd April 2023) - Ginanneschi, Federica; Cioncoloni, David; Capoccitti, Giorgio; Volpi, Nila; Ferretti, Fabio; Giannini, Fabio; Rossi, Alessandro
ABSTRACT: Objectives: Electrophysiology plays a crucial role in Guillain-Barré syndrome (GBS) diagnosis and subtype classification. The aim of our study was to assess the potential role of distal compound muscle action potential (dCMAP) for early differentiation between acute inflammatory demyelinating polyneuropathy (AIDP) and axonal GBS. Methods: We retrospectively reviewed the medical records of 24 subjects with AIDP and 18 subjects with axonal GBS. We built up receiver operating characteristic curves for total dCMAP duration and negative phase of dCMAP duration, in order to derive cut-off values able to differentiate between AIDP and axonal GBS. Results: The total duration of dCMAP was significantly prolonged in AIDP compared to axonal GBS. AUCs, odds ratio and positive predictive values were higher for total duration than for negative peak duration. Nerve conduction parameters in the lower limbs were more sensitive than those in the upper limbs in distinguishing AIDP from axonal GBS. Discussion: Total duration of dCMAP dispersion may capture an adjunctive component of distal demyelination, not measured by the more traditional parameters and may thus represent a useful tool for early differentiation between AIDP and axonal GBS.